Analysis of Symbolic Meaning in Drama Scripts and Its Implications toward Indonesian Language Learning of High School Students - Fuad, Muhammad; Sisi, Nalan Meilia; Suyanto, Edi; Muhammad, Ulul Azmi; Amala, Istiqomah Ahsanu (FKIP Universitas Lampung, 2022)
Analysis of Symbolic Meaning in Drama Scripts and Its Implications in Indonesian Language Learning for Class X Senior High School Students. Objective: This study aims to describe the symbolic meaning of the drama script and its implications for learning Indonesian for class X students. Methods: The analysis of symbolic meaning and its implications uses the eclectic method and the Semiotics perspective of Charles Sanders Pierce. Findings: The results of the study indicate that there is a symbolic meaning that shows a shift in the type of lexical meaning following the meaning of its social function in the drama script. The symbolic meaning is relevant to the learning objectives in Basic Competencies 3.6 Understanding the types of purpose and Basic Competencies 4.6 Using the kinds of importance in sentences. Conclusion: The implications for learning Indonesian can be more flexible in preparing innovative learning tools through drama scripts. Keywords: symbolic meaning, drama script, Indonesian language learning.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202226